DIGITAL TRANSFORMATION OF RETAIL INDUSTRY UNDER THE INFLUENCE OF COVID-19: A CASE STUDY IN CHINA - Chen Zhengping; Nasuha Lee Abdullah; Chen Zheng (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
After the outbreak of the COVID-19, the retail industry has been hit unprecedentedly in all aspects. Obviously, the traditional retail business model is no longer suitable for today’s market environment. This research takes the retailer from Guandong, China, Urban Neighbourhood Ltd as a case study company to analyze the overall situation of retailers in the context of the long-term COVID-19 and identify the business model by using the business model canvas. This research adopts the Business Process Management (BPM) Lifecycle model as the main research methodology. Data collection methods include conversation, observation, interview and questionnaires. Meanwhile fish bone diagram, SPPS and WEKA were the tools used in the analysis. 327 responses were recorded from 400 questionnaires distributed and interviews were conducted to investigate the current situation of the case company. A total of 11 key factors namely, (i)customer segments (ii)shopping channels (iii)classification and placement of commodities. (iv)return service. (v)commodities supply (vi) delivery service (vii) business hours (viii) popularity of promotional activities (ix) Accessibility of the services (x)epidemic prevention work (xi) queue time have been identified to be the factors affecting the performance of Urban Neighbourhood Ltd during the outbreak of COVID-19. Finally, this research proposes the basic idea of digital transformation with a new business model and redesigned a sales process including omnichannel sales and distribution for the company.